Semiclassical decay of monopoles in N=2 gauge theory - Timothy Hollowood (1996)
It is shown how monopoles and dyons decay on curves of marginal stability in the moduli space of vacua at weak coupling in pure N=2 gauge theory with arbitrary gauge group. The analysis involves a semi-classical treatment of the monopole and rests on the fact that the monopole moduli space spaces for a magnetic charge vector equal to a non-simple root enlarge discontinuously at the curves of marginal stability. This enlargement of the moduli space describes the freedom for the monopole to be separated into stable constituent monopoles. Such decays do not occur in the associated theory with N=4 supersymmetry because in this case there exist bound-states at